Religious Tolerance Through the Lens of Halal Dining Experience in Malaysia - Aiedah Abdul Khalek; Mohd Mokhtar, Ros Aiza (Kajian Malaysia, 2022)
Religious tolerance is essential to develop a harmonious coexistence between members of a civilised multi-religious society. This notion is previously observed through a legal perspective, recognition and respect, as well as the absence of discrimination and religious conflict. However, this article looks at a different viewpoint, by utilising the dynamics of halal dining as an analytical tool to examine dimensions of religious tolerance. The study unpacks the religious tolerance experience in halal dining among Muslims and non-Muslims in Peninsular and East Malaysia. We compare the data of religious tolerance in halal dining from both Peninsular and East Malaysian experiences. Data was collected through quantitative surveys and interviews with Muslim and non-Muslim respondents. The findings show that Malaysians practise a high level of tolerance in dining with a few exceptions. These findings exhibit a new dimension of dining as a practical analytical tool, which might have hitherto been neglected in measuring religious tolerance within a multi-religious context.